BRCA1-mutated and basal-like breast cancers have similar aCGH profiles and a high incidence of protein truncating TP53 mutations - Holstege, Henne; Horlings, Hugo M; Velds, Arno; Langerød, Anita; Børresen-Dale, Anne-Lise; van de Vijver, Marc J; Nederlof, Petra M; Jonkers, Jos (BMC cancer, 2010)
Background Basal-like breast cancers (BLBC) are aggressive breast cancers for which, so far, no targeted therapy is available because they typically lack expression of hormone receptors and HER2. Phenotypic features of BLBCs, such as clinical presentation and early age of onset, resemble those of breast tumors from BRCA1 -mutation carriers. The genomic instability of BRCA1 -mutated tumors can be effectively targeted with DNA-damaging agents and poly-(ADP-ribose) polymerase 1 (PARP1) inhibitors. Molecular similarities between BLBCs and BRCA1 -mutated tumors may therefore provide predictive markers for therapeutic response of BLBCs. Methods There are several known molecular features characteristic for BRCA1 -mutated breast tumors: 1) increased numbers of genomic aberrations, 2) a distinct pattern of genomic aberrations, 3) a high frequency of TP53 mutations and 4) a high incidence of complex, protein-truncating TP53 mutations. We compared the frequency of TP53 mutations and the pattern and amount of genomic aberrations between BRCA1 -mutated breast tumors, BLBCs and luminal breast tumors by TP53 gene sequencing and array-based comparative genomics hybridization (aCGH) analysis. Results We found that the high incidence of protein truncating TP53 mutations and the pattern and amount of genomic aberrations specific for BRCA1-mutated breast tumors are also characteristic for BLBCs and different from luminal breast tumors. Conclusions Complex, protein truncating TP53 mutations in BRCA1-mutated tumors may be a direct consequence of genomic instability caused by BRCA1 loss, therefore, the presence of these types of TP53 mutations in sporadic BLBCs might be a hallmark of BRCAness and a potential biomarker for sensitivity to PARP inhibition. Also, our data suggest that a small subset of genomic regions may be used to identify BRCA1-like BLBCs. BLBCs share molecular features that were previously found to be specific for BRCA1-mutated breast tumors. These features might be useful for the identification of tumors with increased sensitivity to (high-dose or dose-dense) alkylating agents and PARP inhibitors.